Trust Repair Discourse In Freedom Writer's Movie Script ( A Discourse Analysis): English - Alia novita (ELITE: Journal of English Language and Literature, 2019)
The use of trust repair discourse in "Freedom Writers" is based on the elements of trust repair discourse which build good relationships because good cooperation can be established in any case. The objective of the study is to describe how trust repair discourse is used in freedom writer’s movie script. The method used in this research is qualitative descriptive to analyze the data. There are two sources of the data in this research, they are movie script as primary data and audiovisual sources as secondary data. The data were collected through watching the movie, reading the script, and selecting the data. Technique of data analysis is done through presenting, describing, interpreting, and concluding the data. The results showed that there were 15 data related to trust repair, consisting of 9 data related to restore positive expectations and 6 data related to counteract negative expectations. The study found that the main character in this movie script uses restore positive expectations and counteract negative expectations in this way the main character gradually gains trust that has been damaged by the ability, integrity and benevolence possessed by the main character so that the main character can restore the sense of trust that has been lost have been corrupted by believing that what they are doing is wrong only brings misery and dishonorable death.